Effects of naphthaleneacetic acid (NAA) and gibberellic acid (GA 3) on fruit morphology, parthenocarpy, alkaloid content and chlorophyll content in bittergourd (Momordica charantia L. 'Makiling') - Tolentino, Melissa F.; Cadiz, Nina M. (2005)
The effects of NAA and GA3 at 0, 20 and 100 ppm on fruit morphology (including parthenocarpy), alkaloid content and chlorophyll content of bittergourd (Momordica charantia L. 'Makiling') were investigated. Results showed that exogenous application of NAA and GA3 at the 5-leaf stage induced parthenocarpy in bittergourd. Fruit length of plants treated with NAA decreased significantly compared with the control. This decrease in fruit size could be due to the absence of seeds as a result of NAA-induced parthenocarpy. In addition, fresh weight of plants treated with 20 ppm NAA significantly decreased while the diameter increased significantly in plants treated with 100 ppm NAA. GA3 treatment did not result in a significant increase in fruit length compared with the control treatment. Fresh weight and diameter significantly decreased in plants treated with 20 ppm GA3. NAA and GA3 treatments slightly increased the alkaloid content of bittergourd fruits, but slightly decreased their foliar alkaloid content. NAA treatment slightly decreased foliar chlorophyll and GA3 slightly increased foliar chlorophyll but not significantly.
Keywords: Momordica charantia; Morphology